1999
DOI: 10.1046/j.1365-2222.1999.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particulates upregulate histamine receptor mRNA and increase histamine‐induced IL‐8 and GM‐CSF production in nasal epithelial cells and endothelial cells

Abstract: These results strongly suggest that DEP accelerates the inflammatory change by not only directly upregulating H1R expression but also increasing histamine-induced IL-8 and GM-CSF production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 36 publications
2
44
0
2
Order By: Relevance
“…Up-regulation of H1R was also observed in patients with allergic rhinitis (6, 7). Terada et al (36) reported that H1R mRNA was increased in human nasal epithelial cells after stimulation with diesel exhaust particles that are known to cause chronic airway diseases. They also showed that histamine stimulation induced production of granulocyte macrophage-colony stimulating factor and interleukin-8 (IL-8) in human nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of H1R was also observed in patients with allergic rhinitis (6, 7). Terada et al (36) reported that H1R mRNA was increased in human nasal epithelial cells after stimulation with diesel exhaust particles that are known to cause chronic airway diseases. They also showed that histamine stimulation induced production of granulocyte macrophage-colony stimulating factor and interleukin-8 (IL-8) in human nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine H 1 receptor (H 1 R) is expressed in both central and peripheral tissues [1], and its expression level is dynamically regulated under various physiological and pathological conditions: upregulation of H 1 Rs or H 1 R mRNA in the electrical foci in the temporal cortex of epileptic patients [2] and in the nasal mucosa of patients with allergic rhinitis [3,4], downregulation of H 1 Rs in the frontal cortex of patients with chronic schizophrenia [5] and in the frontal and temporal areas of patients with Alzheimer's disease [6]. The H 1 R level may be regulated under these conditions by various processes as indicated for other types of G protein-coupled receptors (GPCRs), including modulation of receptor gene transcription [7], mRNA stability [8] and receptor degradation [9], and agonist-induced receptor degradation or receptor downregulation seems to play an important role among these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Terada et al (41) demonstrated that DEPs upregulate the expression of histamine-1 receptor mRNA in human airway epithelial and endothelial cells, and enhance histamine induced increase in IL-8 and granulocyte-macrophage colony-stimulating factor (GM-CSF) production in vitro. Histamine-1 receptor mRNA is markedly increased in patients with allergic rhinitis (42), and a further up-regulation induced by DEP may further enhance the effects of histamine.…”
mentioning
confidence: 99%